PD-1 blockade prevents the progression of oral carcinogenesis. (16th May 2021) - Dong, Yunmei; Wang, Zhen; Mao, Fei; Cai, Luyao; Dan, Hongxia; Jiang, Lu; Zeng, Xin; Li, Taiwen; Zhou, Yu; Chen, Qianming
Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common malignancies in the head and neck with a poor prognosis. Oral cancer development is a multistep process involving carcinogenesis. Though significant advances in cancer immunotherapy over the years, there is lack of evidence for T-cell exhaustion during oral carcinogenesis. Clinical specimens from healthy donors and patients diagnosed with oral leukoplakia (OLK) or OSCC were collected for immunohistochemical staining with PD-L1, CD86, CD8, PD-1 and CTLA-4 antibodies. Meanwhile, chemically induced mouse models of oral carcinogenesis were constructed with 4-nitroquinolone- N -oxide induction. Exhaustion status of T cells was measured by flow cytometry for spleens and by multiplex immunohistochemistry for formalin-fixed paraffin-embedded lesions in multiple stages of oral carcinogenesis. The efficacy of PD-1 blockade with or without cisplatin treatment was evaluated on the mice in precancerous and OSCC stages. We observed higher expression of PD-1 in the human OLK and OSCC tissues compared with the normal, while low expression CTLA-4 in all oral mucosa tissues. Animal experiments showed that the exhausted CD4 + T cells existed much earlier than exhausted CD8 + T cells, and an increased ratio of stem-like exhausted T cells and partially exhausted T cells were detected in the experimental groups. Besides, the expression of immune checkpoint markers (PDCD1, CTLA4 and HAVCR2) was strongly positively correlated with cytokines (IFNG and IL-2). In summary, T-cell exhaustion plays a vital role in oral carcinogenesis, and PD-1 blockade can prevent the progression of oral carcinogenesis. Abstract : In this study, we revealed that exhausted T cells played a vital role in oral carcinogenesis, which could be confirmed by the evidences from clinical specimens and the animal models. And PD-1 blockade can prevent the progression of oral carcinogenesis.